IMPROVEMENT OF THE ENTERPRISE'S INNOVATIVE MANAGEMENT SYSTEM BASED ON STRATEGIC MANAGEMENT (Ustozlar uchun, 2025)
The article discusses the methods of innovative development of construction material production enterprises, the prospects and stages of developing innovative strategies.